Saturday night fever [videorecording (Blu-Ray)] - Wexler, Norman; Travolta, John, 1954-; Gorney, Karen Lynn; Miller, Barry, 1958-; Cali, Joseph, 1950-; Pape, Paul, 1952-; Pescow, Donna (Paramount Pictures, 2017)
All-new Director's Cut celebrating the 40th Anniversary of the iconic film that catapulted John Travolta to superstardom, garnered him an Oscar nomination, and captivated audiences the world over. Travolta commands the screen as Tony Manero, a restless Brooklyn rebel who escapes problems at home and an uncertain future every Saturday night when he shines as king of the disco dance floor. Includes theatrical and director's cut.